2015
DOI: 10.1177/0748233714566873
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the toxic and beneficial effects of lichen extracts in normal and diabetic rats

Abstract: Lichens can be used as a novel bioresource for natural antioxidants. However, there is need for further investigations to validate the lichens used in medicinal remedies. In this study, the effects of Cetraria islandica and Pseudevernia furfuracae lichen species in streptozotocin (STZ)-induced diabetes were evaluated. Diabetic rats were treated with aqueous lichen extracts (250 and 500 mg/kg/day) for 2 weeks starting at 72 h after STZ injection. On the 14th day, animals were anesthetized, and then metabolic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Thus, long-term TV extract (500 mg/kg/d) supplementation had no harmful effects in DIO mice. Çolak et al ( 23 ) also reported that Cetraria islandica and Pseudevernia furfuracae lichen species could be safely used at 500 mg/kg body weight in normal and diabetic rats. These data showed that the decreased body weight and fat mass in TV extract-supplemented mice did not result from the toxicity of the TV extract.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, long-term TV extract (500 mg/kg/d) supplementation had no harmful effects in DIO mice. Çolak et al ( 23 ) also reported that Cetraria islandica and Pseudevernia furfuracae lichen species could be safely used at 500 mg/kg body weight in normal and diabetic rats. These data showed that the decreased body weight and fat mass in TV extract-supplemented mice did not result from the toxicity of the TV extract.…”
Section: Resultsmentioning
confidence: 99%
“…However, the protective effects of the C. islandica extract were insufficient against diabetes-induced pancreatic damage through the formation of oxidative stress. In conclusion, the use of C. islandica could serve as a prompt intervention in the reduction of the risk of type 1 diabetes [80].…”
Section: Diabetes Mellitusmentioning
confidence: 94%
“…Moreover, the aqueous extract of Cetraria islandica decreased the total oxidative stress (TOS) and increased the total antioxidant capacity (TAC) in streptozotocin-induced Diabetes Mellitus type 1 Sprague-Dawley rats [ 118 ]. Using the same model, the aqueous extract of Cetraria islandica (250–500 mg/kg/day) increased the levels of SOD, CAT and GSH, and reduced the levels of MDA [ 16 , 119 , 120 ]. Regarding neuroprotection studies, the protective role of Cetraria islandica and its isolated secondary metabolite fumarprotocetraric acid has been demonstrated in a hydrogen peroxide-induced oxidative stress model on human U373MG astrocytoma cells and human SH-SY5Y neuroblastoma cells.…”
Section: Therapeutic Potentialmentioning
confidence: 99%